ANALISIS STRUKTUR KOTA DI JAWA TERHADAP KONSUMSI BBM DENGAN MENGGUNAKAN BIPLOT - Mudjiastuti Handajani; Bambang Riyanto (Department of Civil Engineering, Diponegoro University, 2010)
ABSTRACK The structure of the city including the variables that affect the city's transportation system. In this case, the structure of the city associated with transport and fuel consumption, which consists of vast areas of administration and woke up, population, population density (net and gross), and GDP (constant and valid). The purpose of this study was to analyze the variable structure of the city, urban transportation systems, and fuel consumption as well as analyzing the relationship between urban transport systems on fuel consumption metropolitan cities, major cities, and towns are in Java. Biplot analysis is descriptive statistical technique multiple dimensions (multivariate) that can be presented visually to present simultaneous observations of n objects and p variables in the space plane (dimension 2), so that the characteristics of variables and object of observation and the relative position between object observations with variables can be analyzed. Biplot analysis results showed that each metropolitan and large cities have different characteristics of urban structure, while the city was relatively similar characteristics. The existence of a positive linear relationship and a very strong connection between population and consumption of premium, that is, the consumption of premium will increase if the population is also increasing. Keywords : City structure, fuel consumption, biplot analysis ABSTRAK Struktur kota termasuk dalam variabel yang mempengaruhi sistem transportasi kota. Dalam hal ini, Struktur kota yang terkait dengan transportasi dan konsumsi bahan bakar, yang terdiri dari luas administrasi daerah dan terbangun, penduduk, kepadatan penduduk (netto dan brutto), dan PDRB (konstan dan berlaku). Tujuan dari penelitian ini adalah untuk menganalisis variabel Struktur kota, sistem transportasi perkotaan, dan konsumsi bahan bakar serta menganalisis hubungan antara sistem transportasi perkotaan terhadap konsumsi bahan bakar kota metropolitan, kota besar, dan kota sedang di Jawa. Analisis Biplot adalah teknik statistika deskriptif dimensi ganda (multivariate) yang dapat disajikan secara visual guna menyajikan secara simultan n obyek pengamatan dan p variabel dalam ruang bidang datar (dimensi 2), sehingga ciri-ciri variabel dan obyek pengamatan serta posisi relatif antar obyek pengamatan dengan variabel dapat dianalisis. Hasil analisa biplot menunjukkan bahwa setiap kota metropolitan dan kota besar memiliki karakteristik Struktur perkotaan yang berbeda, sedangkan kota sedang memiliki karakteristik yang relatif sama. Adanya hubungan linear positif dan sangat kuat antara penduduk dan konsumsi premium, artinya, konsumsi premium akan meningkat jika populasi juga meningkat. Kata kunci: Struktur Kota, Konsumsi BBM, Analisis Biplot